PERANCANGAN VENDOR MANAGEMENT INVENTORY PADA USAHA KAYU - Rohmatulloh, Mohammad Egi; Ilmaniati, Anita (Jurnal Media Teknik dan Sistem Industri, 2019)
Abstract— Distortion of supply chain information in the industry can cause a mismatch between supply and demand, thus causing the bullwhip effect. One method that can be applied to overcome information distortion as the cause of the bullwhip effect is vendor managing inventory (VMI), where the needs of distributors and retail are controlled and monitored by the supplier. This study aims to measure the bullwhip effect on the supply chain at suppliers and producers, and propose VMI designs on supply chains at suppliers and producers. The research was carried out by calculating the value of the demand for the retail, producer and supplier, while the repairs were carried out by forecasting demand by then performing a VMI simulation for recalculating the bullwhip effect. The results showed that the value of the bullwhip effect on suppliers (Mahoni Lestari PD), producers (PD Kurbiti), and retailers (PD Nur Sofi) changed from 1,246, 1,073 and 1,118 (all above the bullwhip effect parameter 1,040) to 1.Key words— Bullwhip effect; Vendor Manage Inventory (VMI); supply chain Abstrak— Distorsi informasi rantai pasok pada industri dapat menyebabkan ketidak sesuaian antara pasokan dan permintaan, sehingga menyebabkan bullwhip effect. Salah satu metode yang dapat diterapkan untuk mengatasi distorsi informasi sebagai penyebab bullwhip effect adalah vendor manage inventory (VMI), dimana kebutuhan distributor dan ritel dikontrol dan dimonitori oleh pihak supplier. Penelitian ini bertujuan untuk mengukur bullwhip effect pada rantai pasok di supplier dan produsen, serta Mengusulkan rancangan VMI pada rantai pasok di supplier dan produsen. Penelitian dilakukan dengan menghitung nilai amplikasi permintaan pada ritel, produsen dan supplier, sedangkan untuk perbaikan dilakukan dengan peramalan permintaan dengan kemudian melakukan simulasi VMI untuk perhitungan kembali bullwhip effect. Hasil penelitian menunjukan bahwa nilai bullwhip effect pada pemasok (PD Mahoni Lestari), produsen (PD Kurbiti), dan retailer (PD Nur Sofi) berubah dari 1,246, 1.073 dan 1,118 (semua diatas bullwhip effect parameter 1,040) menjadi 1.Kata kunci— Bullwhip effect; Vendor Manage Inventory (VMI); rantai pasok